Significance of Vertigo, Imbalance, and Other Minor Symptoms in Hyperacute Treatment of Posterior Circulation Stroke - Kim, Min; Park, So Young; Lee, Sung Eun; Lee, Jin Soo; Hong, Ji Man; Lee, Seong-Joon (Frontiers in Neurology, 2022)
Background This study aimed to determine the clinical significance of acute vestibular syndrome (AVS)/acute imbalance syndrome (AIS) in posterior circulation stroke (PCS) and how it should be addressed in the thrombolysis code. Methods Our institution has recently changed its thrombolysis code from one that is generous to AVS/AIS to one that is exclusive. The subjects in this study were patients with PCS who presented before this transition (May 2016 to April 2018, period 1) and those who presented after (January 2019 to December 2020, period 2) with an onset-to-door time of 4.5 h. Hyperacute stroke treatment was compared between the two periods. The clinical significance of AVS/AIS was evaluated by dichotomizing the patients' clinical severity to minor or major deficits, then evaluating the significance of AVS/AIS in each group. Presenting symptoms of decreased mental alertness, hemiparesis, aphasia (anarthria), or hemianopsia were considered major PCS symptoms, and patients who did not present with these symptoms were considered minor PCS. Results In total, 114 patients presented in period 1 and 114 in period 2. Although the code activation rate was significantly lower in period 2 (72.8% vs. 59.7%), p = 0.04, there were no between-group differences in functional outcomes (mRS score at 3 months; 1 [0–3] vs. 0 [0–3], p = 0.18). In 77 patients with PCS and AVS/AIS, the difference in code activation rate was not significant according to changes in thrombolysis code. In minor PCS, AVS/AIS was associated with lower NIHSS scores, lower early neurological deterioration rates, and favorable outcomes. In major PCS, while AVS/AIS was not associated with outcomes, the majority of cases were prodromal AVS/AIS which simple vertigo and imbalance symptoms were followed by a major PCS symptom. Conclusions This study failed to show differences in outcome in patients with PCS according to how AVS/AIS is addressed in the stroke thrombolysis code. In patients with minor PCS, AVS/AIS was associated with a benign clinical course. Prompt identification of prodromal AVS/AIS is essential.